Evaluation of care burden and caregiving preparedness in caregivers of patients with epilepsy: A sample in eastern Turkey - Turan, Gulcan Bahcecioglu; Dayapoglu, Nuray; Ozer, Zulfunaz (Academic Press Inc Elsevier Science, 2021)
Aim: This study was conducted to evaluate the care burden and caregiving preparedness in caregivers of patients with epilepsy. Methods: This descriptive, cross-sectional study evaluated the caregivers of patients with epilepsy who were referred to the neurology outpatient clinic of a university hospital in Erzurum, eastern Turkey, between February 2020 and February 2021. The study was carried out with 147 volunteers among the patients with epilepsy who were referred to the neurology outpatient clinic between the specified dates. The data were collected with Caregiver Question Form, the Brief Disability Questionnaire (BDQ), the Burden Interview (BI), and the Preparedness for Caregiving Scale (PCS). Results: The mean BI score of the caregivers who participated in the study was 43.14 +/- 18.08, their mean PCS score was 14.12 +/- 7.76, and their mean BDQ score was 10.53 +/- 4.65. In the regression analysis conducted, it was found that being married, having little knowledge of patient care, undertaking all of the roles in caregiving and having caregiving duration of 24 months and longer had a negative effect on PCS total score, while having an undergraduate degree and higher had a positive significant effect. It was found that having an undergraduate degree and higher had a negative effect on BI total score, while all of the roles undertaken in caregiving had a positive significant effect on BI total score. It was found that PCS had a negative significant effect on BI total score (p < 0.001). Conclusion: Caregivers of patients with epilepsy had a moderate level of burden and caregiving preparedness, and the patients cared for had a moderate level of disability. Caregiver burden increased as disability of patients with epilepsy and the tasks undertaken in caregiving increased, whereas burden decreased as caregiver education and caregiving preparedness increased. (c) 2021 Elsevier Inc. All rights reserved.
Keywords: Caregiver; Care burden; Caregiving preparedness; Epilepsy